Synthesis and Application of Zinc Layered Hydroxide: A Short Review - Zuhailimuna Muda; Norlaili Abu Bakar; Wan Rusmawati Wan Mahamod; Syazwan Afif Mohd Zobir; Suyanta Suyanta; Norhayati Hahsim; Illyas Md Isa; Noorshida Mohd Ali; Sharifah Norain Mohd Sharif; Maizatul Najwa Jajuli (Universitas Gadjah Mada, 2023)
Zinc Layered hydroxide (ZLH) is a layered material easily synthesized with a structure identical to brucite-like material. Due to the exchangeable anions in the interlayer compensating for the positive charge of a brucite-type layer, ZLH provides a wide application in many fields. This review focuses on the properties and method of synthesis of ZLH by giving an overview of intercalated guest anion in the interlayer of ZLH. The further discussion involved the application of intercalated guest anion in zinc layered hydroxide layer and its properties as a sensitizer, controlled release biomedical, and agriculture to provide the scientific community for research and development by giving current findings. This brief review also presents the success of anion intercalation for controlled release along with the kinetic model involved, which increases the bioavailability and effectiveness of the nanocomposite on its target. It shows the development of research on ZLH nanocomposites toward the sustainability of human life and the environment. This study implies that it is a source of knowledge for researchers about zinc-layered hydroxide materials involving synthesis methods and their application to produce more beneficial nanomaterials.